Carbon monoxide sensor material, material preparation method and carbon monoxide sensor
By using metal-organic frame composite materials prepared by assembling copper oxide and p-phenylenediamine, the problems of low selectivity, high operating temperature and high cost of existing carbon monoxide sensor materials are solved, and high selectivity, low temperature and low cost of carbon monoxide sensor materials are achieved.
Patent Information
- Application Number
- CN202411741523.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-25
AI Technical Summary
Existing carbon monoxide sensor materials have low selectivity, high operating temperature and high cost.
The metal-organic frame composite material obtained by assembling copper oxide and para-phenylenediamine through coordination bonds is used as the carbon monoxide sensor material. The sensor material with high selectivity, low operating temperature and low cost is prepared by specific preparation methods including dissolution, ice bath polymerization, pH adjustment and activation treatment.
High selective detection of carbon monoxide is achieved, the working temperature can be as low as 50°C and the cost is low, avoiding the problems of high price of electrochemical sensors, low sensitivity of thermal conductivity sensors and high energy consumption of semiconductor oxide sensors in the prior art.
Smart Images

Figure CN119505273A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of gas sensors, and in particular to a carbon monoxide sensor material, a method for preparing the carbon monoxide sensor material, and a carbon monoxide sensor. Background Art
[0002] Environmental pollution caused by carbon monoxide has attracted global attention. Carbon monoxide is a primary gaseous pollution. It is colorless and odorless and difficult for humans to perceive. Inhalation by humans can cause physical discomfort and even affect life and health in severe cases. Therefore, it is very important to detect carbon monoxide in the environment.
[0003] At present, the sensors used to detect carbon monoxide mainly include electrochemical sensors, thermal conductivity sensors, and semiconductor oxide sensors. Among them, electrochemical sensors are relatively expensive, and electrolyte leakage may occur during use, resulting in a shortened lifespan. Thermal conductivity sensors have the problems of low sensitivity and low selectivity. The operating temperature of semiconductor oxide sensors is generally high, generally 200℃-300℃, resulting in high energy consumption. At the same time, semiconductor oxide sensors are usually doped with precious metals Pd or Pt to improve their sensitivity, and the cost is also high.
[0004] Therefore, there is an urgent need for a carbon monoxide sensor material with higher selectivity, lower operating temperature and lower cost. Summary of the invention
[0005] The purpose of the present invention is to overcome the problems of low selectivity, high operating temperature and high cost of existing carbon monoxide sensor materials, and to provide a carbon monoxide sensor material, a material preparation method and a carbon monoxide sensor.
[0006] In order to achieve the above object, the first aspect of the present invention provides a carbon monoxide sensor material, wherein the carbon monoxide sensor material is a metal organic framework composite material assembled by coordination bonds of copper oxide and p-phenylenediamine.
[0007] The second aspect of the present invention provides a method for preparing the carbon monoxide sensor material of the first aspect, the preparation method comprising: dissolving p-phenylenediamine and anhydrous cupric chloride in water to obtain a first solution; dissolving ammonium persulfate in water to obtain a second solution; adding the second solution to the first solution to obtain a third solution, placing the third solution in an ice bath at a preset temperature to polymerize the solution to obtain a dark brown precipitate; Adding glacial acetic acid and NaOH solution to the third solution until the pH reaches a preset pH value to obtain a fourth solution; The fourth solution is allowed to stand to obtain a target precipitate, and the target precipitate is cleaned and dried to obtain a carbon monoxide sensor material.
[0008] In the embodiment of the present application, the molar ratio of p-phenylenediamine to anhydrous cupric chloride is (0.01:1)-(0.2:1).
[0009] In the embodiment of the present application, the molar ratio of ammonium persulfate to p-phenylenediamine is 1:1.
[0010] In an embodiment of the present application, the step of adding the second solution to the first solution comprises: The second solution is added to the first solution by dropwise addition.
[0011] In the embodiment of the present application, the preset temperature is 0°C-5°C.
[0012] In the embodiment of the present application, the preset pH value is 8-9.
[0013] In the embodiment of the present application, after the target precipitate is cleaned and dried, the preparation method further comprises: The target precipitate after washing and drying is activated.
[0014] In the embodiment of the present application, the activation treatment of the target precipitate after washing and drying comprises: The cleaned and dried target precipitate is placed in a tube furnace and activated in an argon environment; The temperature in the tubular furnace is 200°C-550°C, and the argon flow rate in the tubular furnace is 55mL / min-65mL / min.
[0015] A third aspect of the present application provides a carbon monoxide sensor, the carbon monoxide sensor comprising an electrode and the carbon monoxide sensor material of the first aspect; The carbon monoxide sensor material is coated on the electrode.
[0016] The carbon monoxide sensor material provided by the above technical solution is a metal organic framework composite material assembled by copper oxide and p-phenylenediamine through coordination bonds; the carbon monoxide sensor prepared based on the carbon monoxide sensor material has high selectivity for carbon monoxide, low operating temperature and low cost.
[0017] Other features and advantages of the embodiments of the present application will be described in detail in the subsequent specific implementation section. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] The accompanying drawings are used to provide a further understanding of the embodiments of the present application and constitute a part of the specification. Together with the following specific implementations, they are used to explain the embodiments of the present application, but do not constitute a limitation on the embodiments of the present application. In the accompanying drawings: Figure 1 A scanning electron microscope image of a carbon monoxide sensor material according to an embodiment of the present application is schematically shown; Figure 2 The schematic diagram shows a process flow diagram of a method for preparing a carbon monoxide sensor material according to an embodiment of the present application; Figure 3 A schematic diagram showing the sensitivity of a carbon monoxide gas sensor made of an activated material and a carbon monoxide gas sensor made of an unactivated material according to an embodiment of the present application is shown; Figure 4 The schematic diagram schematically shows the sensitivity of the carbon monoxide gas sensor to CO gas of different concentrations according to the embodiment of the present application; Figure 5-Figure 10 The schematic diagram schematically shows the sensitivity of a carbon monoxide gas sensor to various gases according to an embodiment of the present application; Fig.11 and Fig.12 A schematic diagram schematically shows the sensitivity of a carbon monoxide gas sensor to CO gas at different operating temperatures according to an embodiment of the present application; Fig.13 A schematic diagram of a range test result of a carbon monoxide gas sensor according to an embodiment of the present application is schematically shown. DETAILED DESCRIPTION
[0019] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. It should be understood that the specific implementation methods described herein are only used to illustrate and explain the embodiments of the present application, and are not used to limit the embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0020] If there are descriptions involving "first", "second", etc. in the embodiments of the present application, the descriptions of "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or suggesting their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the ability of ordinary technicians in the field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the scope of protection required by this application.
[0021] As described in the background technology, the environmental pollution caused by carbon monoxide has attracted global attention. Carbon monoxide belongs to primary gaseous pollution. It is colorless and odorless and difficult to be perceived by humans. Inhalation by the human body will cause physical discomfort, and in severe cases, it may even affect life and health. Therefore, it is very important to detect carbon monoxide in the environment. At present, the sensors used to detect carbon monoxide mainly include electrochemical sensors, thermal conductivity sensors, and semiconductor oxide sensors. Among them, electrochemical sensors are relatively expensive, and electrolyte leakage may occur during use, resulting in a shortened life. Thermal conductivity sensors have the problems of low sensitivity and low selectivity. The operating temperature of semiconductor oxide sensors is generally high, generally 200℃-300℃, resulting in high energy consumption. At the same time, semiconductor oxide sensors are usually doped with precious metals Pd or Pt to improve their sensitivity, and the cost is also high.
[0022] In view of this, in one embodiment, the present application provides a carbon monoxide sensor material, which can be used to manufacture a carbon monoxide sensor. The carbon monoxide sensor material is a metal organic framework composite material assembled by copper oxide and p-phenylenediamine through coordination bonds.
[0023] Among them, the carbon monoxide sensor material is a metal organic framework composite material assembled by copper oxide and p-phenylenediamine through coordination bonds. It can be understood that: copper oxide and p-phenylenediamine are assembled by coordination bonds to obtain a composite material with a metal organic framework structure, and the composite material with a metal organic framework structure is the carbon monoxide sensor material.
[0024] In the embodiments of the present application, the carbon monoxide sensor material has a large specific surface area and abundant surface active sites.
[0025] like Figure 1 As shown in FIG. 1 , a scanning electron microscope image (SEM image) of a specific carbon monoxide sensor material in the embodiment of the present application is shown. When preparing the carbon monoxide sensor material, the molar ratio of p-phenylenediamine to anhydrous cupric chloride is 1:10. Figure 1It can be seen that the material is accumulated in a flower ball shape, has a larger specific surface area and porosity, and provides a good channel for gas transmission. In addition, the sensor material has abundant surface active sites, so that the carbon monoxide sensor material exhibits excellent gas sensing performance when used for detection.
[0026] It can be understood that by adopting the carbon monoxide sensor material provided in the embodiment of the present application, the carbon monoxide sensor material is a metal organic framework composite material assembled by copper oxide and para-phenylenediamine through coordination bonds; the carbon monoxide sensor prepared based on the carbon monoxide sensor material has higher selectivity for carbon monoxide, lower operating temperature and lower cost.
[0027] In addition, compared with other sensor materials such as carbon matrix, gel matrix, metal particles, metal oxides and transition metals, the carbon monoxide sensor material provided in the above embodiment of the present application has more abundant surface active sites and higher stability. At the same time, the carbon monoxide sensor material provided in the above embodiment of the present application can also overcome the defects of most metal oxide carbon monoxide sensors with high operating temperature and unable to achieve low temperature carbon monoxide response. The operating temperature of the carbon monoxide sensor material provided in the above embodiment of the present application can be as low as 50°C.
[0028] Based on the carbon monoxide sensor material provided in the above embodiment of the present application, the embodiment of the present application also provides a method for preparing the carbon monoxide sensor material. Figure 2 As shown, the preparation method may include the following steps: Step 101, dissolving p-phenylenediamine and anhydrous cupric chloride in water to obtain a first solution.
[0029] The molar ratio of p-phenylenediamine to anhydrous cupric chloride may be (0.01:1)-(0.2:1). For example, it may be 0.01:1; 0.02:1; 0.05:1; 0.08:1; 0.1:1; 0.15:1; 0.18:1; 0.2:1 and any ratio in the range formed by any two of these ratios. The water used to dissolve p-phenylenediamine and anhydrous cupric chloride may be deionized water.
[0030] In the first solution, the amount of deionized water matches the amount of p-phenylenediamine and anhydrous cupric chloride fed, and is sufficient to completely dissolve p-phenylenediamine and anhydrous cupric chloride.
[0031] In a specific implementation, in order to fully dissolve p-phenylenediamine and anhydrous cupric chloride, after adding p-phenylenediamine and anhydrous cupric chloride into water, ultrasound can be used to promote the dissolution of p-phenylenediamine and anhydrous cupric chloride, thereby obtaining a first solution. The specific duration of ultrasound can be set according to the dissolution situation, for example, the duration of ultrasound can be 30 min-60 min.
[0032] Step 102, dissolving ammonium persulfate in water to obtain a second solution.
[0033] The water used to dissolve the ammonium persulfate may specifically be deionized water.
[0034] In the second solution, the amount of deionized water matches the amount of ammonium persulfate added and can completely dissolve the ammonium persulfate.
[0035] The molar ratio of ammonium persulfate to p-phenylenediamine may be 1:1.
[0036] Step 103, adding the second solution to the first solution to obtain a third solution, placing the third solution at a preset temperature for ice bath polymerization to obtain a black-brown precipitate.
[0037] In the specific implementation, in order to make the reaction sufficient and obtain the carbon monoxide sensor material with the above-mentioned morphology and performance, the second solution can be added to the first solution by dripping. Specifically, a 1mL dropper can be used to drip at a uniform speed of 1 drop / s, and 1 drop is about 0.05mL; that is, the dripping speed is about 0.05mL / s.
[0038] The preset temperature may be 0° C.-5° C. Taking the ice bath condition as an example, in practical applications, ice cubes are usually continuously added to the water bath to maintain the temperature in the water bath at 0° C.-5° C. That is, during the ice bath polymerization process, the temperature in the water bath fluctuates and changes within the temperature range of 0° C.-5° C.
[0039] The ice bath polymerization time may be 6 h to 8 h.
[0040] Step 104, adding glacial acetic acid and NaOH solution to the third solution until the pH reaches a preset pH value to obtain a fourth solution.
[0041] That is, glacial acetic acid and NaOH solution were added to the third solution producing the black-brown precipitate.
[0042] In a specific implementation, adding glacial acetic acid and NaOH solution to the third solution may include: first adding glacial acetic acid to the third solution, and then adding NaOH solution to the third solution.
[0043] The amount of glacial acetic acid added is 3 mL to 5 mL, which can provide acetate ions to prevent precipitation of impurities.
[0044] The concentration of the NaOH solution may be 0.3 mol / L-0.8 mol / L. More preferably, the concentration of the NaOH solution may be 0.5 mol / L.
[0045] The preset pH value is 8-9, and more preferably, the preset pH value may be 8.5.
[0046] Step 105, allowing the fourth solution to stand to obtain a target precipitate, and washing and drying the target precipitate to obtain a carbon monoxide sensor material.
[0047] Before the fourth solution is placed in a static state, it may be subjected to magnetic stirring to make the reaction more complete. The speed of the magnetic stirring may be 350 r / min-500 r / min, and the duration of the magnetic stirring may be 3 h-5 h. The duration of the third solution being placed in a static state may be 3 h-5 h.
[0048] The process of washing the target precipitate may include: washing the target precipitate alternately with anhydrous ethanol and deionized water, repeating 2-3 times until the precipitate is washed to neutrality. After each washing, the precipitate is separated by centrifugation. Then, the precipitate obtained from the last washing is placed in a blast drying oven for drying. The centrifugal speed may be 8000r / min-10000r / min, and the drying temperature may be 60°C.
[0049] In practical applications, in order to further improve the activity, stability and selectivity of the carbon monoxide sensor material to carbon monoxide gas, after step 105, the preparation method provided in the embodiment of the present application may further include step 106, activating the target precipitate after washing and drying.
[0050] In a specific implementation, the target precipitate after cleaning and drying is activated, which may include: placing the target precipitate obtained after cleaning and drying in a tube furnace and activating it in an argon environment.
[0051] Specifically, the target precipitate obtained after washing and drying is ground into powder, and then placed in a tube furnace for activation.
[0052] The heating rate of the tubular furnace can be 2°C / min-4°C / min. During the activation process, the temperature in the tubular furnace can be 200°C-550°C, the argon flow rate in the tubular furnace can be 55mL / min-65mL / min, and the activation time can be 2.5-3.5h, preferably 3h.
[0053] The carbon monoxide sensor material provided in the above embodiment of the present application is obtained through the above process. The carbon monoxide sensor material can also be called copper oxide-polyparaphenylenediamine carbon monoxide sensor material, denoted as CuO-PPDA carbon monoxide sensor material.
[0054] It can be understood that the carbon monoxide sensor material preparation method provided in the embodiment of the present application can be used to prepare the carbon monoxide sensor material with high selectivity for carbon monoxide, low operating temperature and low cost in the above embodiment of the present application. In addition, the preparation method has a simple process and high repeatability.
[0055] Based on the carbon monoxide sensor material provided in the above embodiment of the present application, the embodiment of the present application further provides a carbon monoxide sensor. The carbon monoxide sensor comprises an electrode and the carbon monoxide sensor material provided in the above embodiment of the present application, wherein the carbon monoxide sensor material is coated on the electrode.
[0056] In practical applications, the carbon monoxide sensor material can be ground with deionized water or alcohol for about 15 minutes, and then the ground material can be applied to the hexagonal plate electrode of the gold electrode and aged for 48 hours at 54 mA to prepare the carbon monoxide sensor.
[0057] It can be understood that, since the carbon monoxide sensor is made of the carbon monoxide sensor material provided by the above embodiment of the present application, the carbon monoxide sensor has higher selectivity for carbon monoxide, lower operating temperature and lower cost.
[0058] The following will be combined with specific examples and comparative examples to illustrate the scheme provided in the examples of the present application. It should be understood that the following examples are only some specific implementation methods and do not represent improper limitations on the scheme of the present application.
[0059] Example 1 0.108 g of p-phenylenediamine and 1.33 g of anhydrous copper chloride were dissolved in 30 mL of deionized water and ultrasonicated for 45 min to obtain a first solution.
[0060] 228.2 mg of ammonium persulfate was dissolved in 10 mL of deionized water to obtain a second solution.
[0061] The second solution was added dropwise to the first solution to obtain the third solution, and a 1 mL dropper was used to uniformly add the solution at a rate of 1 drop / s (about 0.05 mL / s). The third solution was placed in an ice bath at 0°C-5°C for polymerization for 6 hours to obtain a black-brown precipitate. The ice bath temperature fluctuated within the range of 0°C-5°C.
[0062] Then, 5 mL of glacial acetic acid was added to the third solution producing a dark brown precipitate, and then a pre-prepared NaOH solution (concentration of 0.5 mol / L) was added until the pH value reached 8.5 to obtain a fourth solution.
[0063] The fourth solution was subjected to magnetic stirring at a speed of 400 r / min for 4 hours, and then allowed to stand for 4 hours to obtain a target precipitate. The target precipitate was centrifugally washed with anhydrous ethanol and deionized water until neutral, at a centrifugal speed of 8000 r / min. The washed target precipitate was dried in a blast drying oven at 60°C, and ground into powder for later use.
[0064] The powder obtained by grinding above was ground with deionized water for 15 minutes, then brushed onto the hexagonal plate electrode of the gold electrode, aged for 48 hours at 54 mA to prepare a carbon monoxide gas sensor, and 50ppm, 100ppm, 200ppm, 300ppm, and 400ppm of CO gas were introduced at an operating temperature of 120℃, and the gas sensing performance was as follows: Figure 3 shown.
[0065] Example 2 0.108 g of p-phenylenediamine and 1.33 g of anhydrous copper chloride were weighed and dissolved in 30 mL of deionized water, and ultrasonicated for 45 min to obtain a first solution.
[0066] 228.2 mg of ammonium persulfate was dissolved in 10 mL of deionized water to obtain a second solution.
[0067] The second solution was added dropwise to the first solution to obtain the third solution, and a 1 mL dropper was used to uniformly add the solution at a rate of 1 drop / s (about 0.05 mL / s). The third solution was placed in an ice bath at 0°C-5°C for polymerization for 6 hours to obtain a black-brown precipitate. The ice bath temperature fluctuated within the range of 0°C-5°C.
[0068] Then, 5 mL of glacial acetic acid was added to the third solution producing a dark brown precipitate, and then a pre-prepared NaOH solution (with a concentration of 0.5 mol / L) was added until the pH value reached 8.5 to obtain a fourth solution.
[0069] The fourth solution was subjected to magnetic stirring at a speed of 400 r / min for 4 hours, and then allowed to stand for 4 hours to obtain the target precipitate. The target precipitate was centrifuged and washed with anhydrous ethanol and deionized water until it was neutral at a centrifugal speed of 8000 r / min. The washed target precipitate was dried at 60° C. in a blast drying oven and ground into powder for later use.
[0070] The powder obtained by grinding as above was placed in a porcelain boat, heated to 500° C. in a tube furnace at a rate of 3° C. / min for activation for 3 h, and naturally cooled to room temperature to obtain the CuO-PPDA carbon monoxide sensor material.
[0071] The CuO-PPDA carbon monoxide sensor material was ground with deionized water for 15 minutes, then brushed onto the hexagonal plate electrode of the gold electrode, aged at 54 mA for 48 hours to prepare a carbon monoxide gas sensor, and 50ppm, 100ppm, 200ppm, 300ppm, and 400ppm of CO gas were introduced at an operating temperature of 120℃, and the gas sensing performance was as follows: Figure 3 and Figure 4 shown.
[0072] Example 3 0.162 g of p-phenylenediamine and 1.33 g of anhydrous cupric chloride were weighed and dissolved in 30 mL of deionized water, and ultrasonicated for 45 min to obtain a first solution.
[0073] 342.3 mg of ammonium persulfate was dissolved in 10 mL of deionized water to obtain a second solution.
[0074] The second solution was added dropwise to the first solution to obtain the third solution, and a 1 mL dropper was used to uniformly add the solution at a rate of 1 drop / s (about 0.05 mL / s). The third solution was placed in an ice bath at 0°C-5°C for polymerization for 6 hours to obtain a black-brown precipitate. The ice bath temperature fluctuated within the range of 0°C-5°C.
[0075] Then, 5 mL of glacial acetic acid was added to the third solution producing a dark brown precipitate, and then a pre-prepared NaOH solution (with a concentration of 0.5 mol / L) was added until the pH value reached 8.5 to obtain a fourth solution.
[0076] The fourth solution was subjected to magnetic stirring at a speed of 400 r / min for 4 hours, and then allowed to stand for 4 hours to obtain a target precipitate. The target precipitate was centrifugally washed with anhydrous ethanol and deionized water until neutral, at a centrifugal speed of 8000 r / min. The washed target precipitate was dried in a blast drying oven at 60°C, and ground into powder for later use.
[0077] The powder obtained by grinding as above was placed in a porcelain boat, heated to 500° C. in a tube furnace at a rate of 3° C. / min for activation for 3 h, and naturally cooled to room temperature to obtain the CuO-PPDA carbon monoxide sensor material.
[0078] The CuO-PPDA carbon monoxide sensor material was ground with deionized water for 15 minutes, then brushed onto the hexagonal plate electrode of the gold electrode, aged at 54 mA for 48 hours to prepare a carbon monoxide gas sensor, and 50ppm, 100ppm, 200ppm, 300ppm, and 400ppm of CO gas were introduced at an operating temperature of 120℃, and the gas sensing performance was as follows: Figure 4 shown.
[0079] Example 4 0.108 g of p-phenylenediamine and 1.33 g of anhydrous copper chloride were dissolved in 30 mL of deionized water and ultrasonicated for 45 min to obtain a first solution.
[0080] 228.2 mg of ammonium persulfate was dissolved in 10 mL of deionized water to obtain a second solution.
[0081] The second solution was added dropwise to the first solution to obtain the third solution, and a 1 mL dropper was used to uniformly add the solution at a rate of 1 drop / s (about 0.05 mL / s). The third solution was placed in an ice bath at 0°C-5°C for polymerization for 6 hours to obtain a black-brown precipitate. The ice bath temperature fluctuated within the range of 0°C-5°C.
[0082] Then, 5 mL of glacial acetic acid was added to the third solution producing a dark brown precipitate, and then a pre-prepared NaOH solution (with a concentration of 0.5 mol / L) was added until the pH value reached 8.5 to obtain a fourth solution.
[0083] The fourth solution was subjected to magnetic stirring at a speed of 400 r / min for 4 hours, and then allowed to stand for 4 hours to obtain a target precipitate. The target precipitate was centrifugally washed with anhydrous ethanol and deionized water until neutral, at a centrifugal speed of 8000 r / min. The washed target precipitate was dried in a blast drying oven at 60°C, and ground into powder for later use.
[0084] The powder obtained by grinding as above was placed in a porcelain boat, heated to 500° C. in a tube furnace at a rate of 3° C. / min for activation for 3 h, and naturally cooled to room temperature to obtain the CuO-PPDA carbon monoxide sensor material.
[0085] The CuO-PPDA carbon monoxide sensor material was ground with deionized water for 15 minutes, then brushed onto the hexagonal plate electrode of the gold electrode, and aged for 48 hours at 54 mA to prepare a carbon monoxide gas sensor, and CO gas with concentrations of 50ppm, 100ppm, 200ppm, 300ppm, and 400ppm, H2 gas with concentrations of 50ppm, 100ppm, 200ppm, 300ppm, and 400ppm, C2H4 gas with concentrations of 50ppm, 100ppm, 200ppm, 300ppm, and 400ppm, CO2 gas with concentrations of 50ppm, 100ppm, 200ppm, 300ppm, and 400ppm, and CH4 gas with concentrations of 50ppm, 100ppm, 200ppm, 300ppm, and 400ppm were introduced respectively. The sensitivity of the carbon monoxide gas sensor to different gases under the working temperature of 120°C can be shown as follows. Figure 5-Figure 10 shown.
[0086] Example 5 0.108 g of p-phenylenediamine and 1.33 g of anhydrous copper chloride were dissolved in 30 mL of deionized water and ultrasonicated for 45 min to obtain a first solution.
[0087] 228.2 mg of ammonium persulfate was dissolved in 10 mL of deionized water to obtain a second solution.
[0088] The second solution was added dropwise to the first solution to obtain the third solution, and a 1 mL dropper was used to uniformly add the solution at a rate of 1 drop / s (about 0.05 mL / s). The third solution was placed in an ice bath at 0°C-5°C for polymerization for 6 hours to obtain a black-brown precipitate. The ice bath temperature fluctuated within the range of 0°C-5°C.
[0089] Then, 5 mL of glacial acetic acid was added to the third solution producing a dark brown precipitate, and then a pre-prepared NaOH solution (with a concentration of 0.5 mol / L) was added until the pH value reached 8.5, to obtain a fourth solution.
[0090] The fourth solution was subjected to magnetic stirring at a speed of 400 r / min for 4 hours, and then allowed to stand for 4 hours to obtain a target precipitate. The target precipitate was centrifugally washed with anhydrous ethanol and deionized water until neutral, at a centrifugal speed of 8000 r / min. The washed target precipitate was dried in a blast drying oven at 60°C, and ground into powder for later use.
[0091] The powder obtained by grinding as above was placed in a porcelain boat, heated to 500° C. in a tube furnace at a rate of 3° C. / min for activation for 3 h, and naturally cooled to room temperature to obtain the CuO-PPDA carbon monoxide sensor material.
[0092] The CuO-PPDA carbon monoxide sensor material was ground with deionized water for 15 minutes, then brushed onto the hexagonal flat electrode of the gold electrode, and aged for 48 hours at 54 mA to prepare a carbon monoxide gas sensor. At a working temperature of 50°C, 50ppm, 100ppm, 200ppm, 300ppm, and 400ppm of CO gas were introduced respectively, at a working temperature of 60°C, 50ppm, 100ppm, 200ppm, 300ppm, and 400ppm of CO gas were introduced respectively, at a working temperature of 90°C, 50ppm, 100ppm, 200ppm, 300ppm, and 400ppm of CO gas were introduced respectively, at a working temperature of 120°C, sensitivities can be shown as follows. Fig.11 and Fig.12 shown.
[0093] Example 6 0.108 g of p-phenylenediamine and 1.33 g of anhydrous copper chloride were dissolved in 30 mL of deionized water and ultrasonicated for 45 min to obtain a first solution.
[0094] 228.2 mg of ammonium persulfate was dissolved in 10 mL of deionized water to obtain a second solution.
[0095] The second solution was added dropwise to the first solution to obtain the third solution, and a 1 mL dropper was used to uniformly add the solution at a rate of 1 drop / s (about 0.05 mL / s). The third solution was placed in an ice bath at 0°C-5°C for polymerization for 6 hours to obtain a black-brown precipitate. The ice bath temperature fluctuated within the range of 0°C-5°C.
[0096] Then, 5 mL of glacial acetic acid was added to the third solution producing a dark brown precipitate, and then a pre-prepared NaOH solution (with a concentration of 0.5 mol / L) was added until the pH value reached 8.5 to obtain a fourth solution.
[0097] The fourth solution was subjected to magnetic stirring at a speed of 400 r / min for 4 hours, and then allowed to stand for 4 hours to obtain a target precipitate. The target precipitate was centrifugally washed with anhydrous ethanol and deionized water until neutral, at a centrifugal speed of 8000 r / min. The washed target precipitate was dried in a blast drying oven at 60°C, and ground into powder for later use.
[0098] The powder obtained by grinding as above was placed in a porcelain boat, heated to 500° C. in a tube furnace at a rate of 3° C. / min for activation for 3 h, and naturally cooled to room temperature to obtain the CuO-PPDA carbon monoxide sensor material.
[0099] The CuO-PPDA carbon monoxide sensor material was ground with deionized water for 15 minutes, then brushed onto the hexagonal plate electrode of the gold electrode and aged for 48 hours at 54 mA to prepare a carbon monoxide gas sensor. The carbon monoxide gas sensor was tested for 10000 ppm CO. The test results are as follows: Fig.13 shown.
[0100] Comparative Example 1 0 g of p-phenylenediamine and 1.33 g of anhydrous copper chloride were dissolved in 30 mL of deionized water and ultrasonicated for 45 min to obtain a first solution.
[0101] 228.2 mg of ammonium persulfate was dissolved in 10 mL of deionized water to obtain a second solution.
[0102] The second solution was added dropwise to the first solution to obtain the third solution, and a 1 mL dropper was used to uniformly add the solution at a rate of 1 drop / s (about 0.05 mL / s). The third solution was placed in an ice bath at 0°C-5°C for 6 hours, wherein the ice bath temperature fluctuated within the range of 0°C-5°C.
[0103] Then, 5 mL of glacial acetic acid was added to the third solution, and then a pre-prepared NaOH solution (concentration of 0.5 mol / L) was added until the pH was 8.5 to obtain a fourth solution.
[0104] The fourth solution was subjected to magnetic stirring at a speed of 400 r / min for 4 hours, and then allowed to stand for 4 hours to obtain a precipitate. The precipitate was centrifugally washed with anhydrous ethanol and deionized water until neutral, at a centrifugal speed of 8000 r / min. The washed precipitate was dried in a blast drying oven at 60° C. and ground into powder for later use.
[0105] The powder obtained by grinding as above was placed in a porcelain boat, heated to 500° C. in a tube furnace at a rate of 3° C. / min for activation for 3 h, and naturally cooled to room temperature to obtain the CuO carbon monoxide sensor material.
[0106] The CuO carbon monoxide sensor material was ground with deionized water for 15 minutes, then brushed onto the hexagonal plate electrode of the gold electrode, aged for 48 hours at 54 mA to prepare a gas sensor, and 50 ppm, 100 ppm, 200 ppm, 300 ppm, and 400 ppm of CO gas were introduced at a working temperature of 120 °C. The gas sensing performance was as follows: Figure 4 shown.
[0107] Depend on Figure 3 (Corresponding to Example 1 and Example 2) It can be seen that the sensor made after the material is activated has better gas sensing performance.
[0108] Depend on Figure 4 (Corresponding to Example 2, Example 3 and Comparative Example 1) It can be seen that the change in the dosage of p-phenylenediamine will affect the gas-sensitive performance of the sensor. When the molar ratio of p-phenylenediamine (represented by A in the figure) to anhydrous cupric chloride (represented by B in the figure) is 0.1:1, the sensor has a better response effect to CO gas.
[0109] Depend on Figure 5-Figure 10 It can be seen that the CuO-PPDA carbon monoxide sensor material provided in the embodiment of the present application has high selectivity for CO gas.
[0110] Depend on Fig.11 It can be seen that with the increase of CO gas concentration, the sensitivity of the sensor gradually increases. When the working temperature is 120℃, the response sensitivity of 400ppmCO is 287.2%. Fig.12 It can be seen that at an operating temperature of 50°C, as the CO gas concentration increases, the sensor sensitivity gradually increases. When the CO concentration is as low as 50ppm, the sensor still has a response sensitivity of 22.7%. Therefore, the CuO-PPDA carbon monoxide sensor provided in this embodiment has good gas sensing performance at low temperatures.
[0111] Depend on Fig.13 It can be seen that when the operating temperature is 120°C, the sensor resistance change gradually increases as the gas concentration increases from 1000ppm to 10000ppm, and the sensitivity is highest at 10000ppm. From the resistance change curve, it can be seen that there is a certain linear relationship between the sensitivity and the gas concentration within a certain range. Therefore, the CuO-PPDA carbon monoxide sensor provided in the embodiment of the present application has stable performance and a wide range, and the test range can reach 10000ppm at 120°C.
[0112] It should also be noted that the endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this article.
[0113] The terms "include", "comprising" or any other variation thereof are intended to cover non-exclusive inclusion, so that a process, method, commodity or apparatus comprising a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, commodity or apparatus. In the absence of more restrictions, an element defined by the phrase "comprising a ..." does not exclude the presence of other identical elements in the process, method, commodity or apparatus comprising the element.
[0114] The above are only embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application should be included within the scope of the claims of the present application.
Claims
1. A carbon monoxide sensor material, characterized in that: The carbon monoxide sensor material is a metal organic framework composite material assembled by copper oxide and p-phenylenediamine through coordination bonds.
2. A method for preparing the carbon monoxide sensor material according to claim 1, characterized in that: The preparation method comprises: dissolving p-phenylenediamine and anhydrous cupric chloride in water to obtain a first solution; dissolving ammonium persulfate in water to obtain a second solution; adding the second solution to the first solution to obtain a third solution, placing the third solution in an ice bath at a preset temperature to polymerize the solution to obtain a dark brown precipitate; Adding glacial acetic acid and NaOH solution to the third solution until the pH reaches a preset pH value to obtain a fourth solution; The fourth solution is allowed to stand to obtain a target precipitate, and the target precipitate is cleaned and dried to obtain a carbon monoxide sensor material.
3. The preparation method according to claim 2, characterized in that: The molar ratio of p-phenylenediamine to anhydrous cupric chloride is (0.01:1)-(0.2:1).
4. The preparation method according to claim 2, characterized in that: The molar ratio of ammonium persulfate to p-phenylenediamine is 1:
1.
5. The preparation method according to claim 2, characterized in that: The step of adding the second solution to the first solution comprises: The second solution is added to the first solution by dropwise addition.
6. The preparation method according to claim 2, characterized in that: The preset temperature is 0°C-5°C.
7. The preparation method according to claim 2, characterized in that: The preset pH value is 8-9.
8. The preparation method according to claim 2, characterized in that: After the target precipitate is cleaned and dried, the preparation method further comprises: The target precipitate after washing and drying is activated.
9. The preparation method according to claim 8, characterized in that: The step of activating the washed and dried target precipitate comprises: The cleaned and dried target precipitate is placed in a tube furnace and activated in an argon environment; The temperature in the tubular furnace is 200°C-550°C, and the argon flow rate in the tubular furnace is 55mL / min-65mL / min.
10. A carbon monoxide sensor, characterized in that: The carbon monoxide sensor comprises an electrode and the carbon monoxide sensor material according to claim 1; The carbon monoxide sensor material is coated on the electrode.